Seeing and Hearing the Other: A Jewish Israeli Teacher Grapples with Arab Students' Underachievement and the Exclusion of Their Voices - Hager, Tamar (Radical Teacher, 2015)
This paper addresses my political and pedagogical resistance to the institutional discrimination of Palestinian Arab students in Israeli academia. Describing my instinctive negative reactions (frustration, helplessness, anger) towards what seems at first sight as their reluctance to study, I go on to criticize my own and other lecturers' tendency to blame the victim by analyzing the structural, cultural, political and social obstacles encountered by Arab students in Israeli institutions of higher education. The paper mainly focuses on the story of my resistance to this prevailing social and political structure. Adopting feminist critical pedagogy in my course "Representing Disability in Literature and the Cinema", I have created a space for my Arab students to overcome at least temporarily their repression by the Israeli academic system. The process of empowerment and the subsequent educational transformative and liberating exchange has enabled all participants to grant Arabs' transparent and excluded knowledge a significant social, cultural and political place, thus creating new and more culturally sensitive knowledge. Confronting the empowering effects of this method, I conclude my paper by suggesting some explanations as to the rarity of critical feminist pedagogies in Israeli academia.